Financial crisis, speculative bubbles and the functioning of financial markets - Roman Horvarth (Kiel University, FinMaP - Financial Distortions and Macroeconomic Performance, 2016)
[Introduction] The recent global financial crisis has showed us how extremely costly financial crises are in terms of economic activity and overall welfare of citizens. It affected strongly the stability of selected European financial institutions as well as the debt management of various governments in Europe. The European Union has undertaken a vast series of steps to safeguard financial stability in Europe, both in the way how financial market supervision is institutionally structured and also in the way how financial market supervision is implemented. Macroprudential policies, which focus on promoting stability of financial system as a whole, has become to forefront. The financial crisis also materialized strongly in macroeconomic stability. The European Central Bank needed to implement large-scale non-standard monetary policy measures to support the euro area economic activity, to improve the functioning of monetary policy transmission mechanism and to reduce deflationary risks. Despite all the steps undertaken in safeguarding financial stability coupled with accommodative monetary policy, we still cannot say that the global financial crisis or its effects are over. Having the enormously negative effects of financial crises in mind, several attendant - both general and specific - questions for academia as well as for policy makers arise. [...]
info:eu-repo/grantAgreement/EC/FP7/612955
Keywords: 330